Frank Einstein and the Bio-action Gizmo - Scieszka, Jon (New York : Amulet Books, 2017)
Boy genius and inventor Frank Einstein and his robot pals Klink (intelligent) and Klank (sort-of intelligent) study the science of ecology and conservation as they try to stop classmate and archrival T. Edison and his loggers from destroying the Midville Forest Preserve.
Keywords: Inventors -- Juvenile fiction; Robots -- Juvenile fiction; Ecology -- Juvenile fiction; Nature conservation -- Juvenile fiction; Inventors -- Fiction; Robots -- Fiction; Ecology -- Fiction; Conservation of natural resources -- Fiction; Science fiction; Humorous Stories; Science fiction; Humorous fiction